Amphiphobic nanocellulose-modified paper: fabrication and evaluation. Issue 16 (2nd February 2016) - Phanthong, Patchiya; Guan, Guoqing; Karnjanakom, Surachai; Hao, Xiaogang; Wang, Zhongde; Kusakabe, Katsuki; Abudula, Abuliti
Abstract : Amphiphobic nanocellulose-modified paper with high durability is successfully fabricated using a facile two-step method. Abstract : Amphiphobic nanocellulose-modified paper with high durability is successfully fabricated using a facile two-step method. Firstly, nanocellulose-modified paper is prepared through dipping filter paper, i.e., glass microfiber (GM) filter paper and polytetrafluoroethylene (PTFE) filter paper in a dilute nanocellulose dispersed solution. Subsequently, the nanocellulose-coated paper is treated with trichloro(1 H, 1 H, 2 H, 2 H -tridecafluoro- n -octyl)silane (FOTS) via chemical vapor deposition. The obtained paper is found to have superhydrophobicity and oleophobicity, repelling both polar and non-polar liquids, on which the drops of water and non-polar liquids with high molecular weight become marble shaped, and the contact angles of water and n -hexadecane reach 156° and 144°, respectively. Furthermore, such amphiphobic nanocellulose-modified papers exhibit excellent surface durability in several environments including at various temperatures, and in acid and alkaline solutions, salt solutions and seawater. In addition, such amphiphobic nanocellulose-modified papers show good repellant properties for several kinds of liquids from our daily life. With outstanding protection to a diverse range of liquids, the amphiphobic nanocellulose-modified paper can be applied in the fields of self-cleaning, anti-bacterial, and anti-corrosion materials.